2002
DOI: 10.1067/mva.2002.119228
|View full text |Cite
|
Sign up to set email alerts
|

Success of thrombolysis as a predictor of outcome in acute thrombosis of popliteal aneurysms

Abstract: Preoperative thrombolysis followed by bypass grafting is a valid treatment option for patients who can withstand an additional period of ischemia that does not require immediate revascularization and intraoperative lysis. Lytic failure identifies patients with a highly compromised runoff who are probably best treated by means of subsequent amputation, without any attempts at bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 28 publications
1
28
0
9
Order By: Relevance
“…Similarly, Sarcina et al , in 67 patients, reported 10‐year patency and LS rates of 78.2 and 87.4%, respectively, in asymptomatic patients, compared with 67.2 and 74.6% in patients with critically ischaemic limbs 19 . Other authors have reported that no limb loss occurred after operative treatment in asymptomatic patients 7,13,18,23 …”
Section: Management Optionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, Sarcina et al , in 67 patients, reported 10‐year patency and LS rates of 78.2 and 87.4%, respectively, in asymptomatic patients, compared with 67.2 and 74.6% in patients with critically ischaemic limbs 19 . Other authors have reported that no limb loss occurred after operative treatment in asymptomatic patients 7,13,18,23 …”
Section: Management Optionsmentioning
confidence: 89%
“…19 Other authors have reported that no limb loss occurred after operative treatment in asymptomatic patients. 7,13,18,23 Various approaches can be taken in the surgical repair of PPA. A medial approach is often used in limbs with acute and chronic ischaemias.…”
Section: Surgical Interventionmentioning
confidence: 99%
“…Overall, in patients with PAA, limbthreatening ischemia has been documented to occur in 17-46% and rupture in 3%. 6,8,[16][17][18][19][20][21] Limb loss from complications of PAA has been observed in as high as 67%. 7,[22][23][24][25] Some have suggested reserving operation for only those with symptoms who were deemed appropriate surgical candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have even recommended primary amputation when thrombolysis fails to restore tibial vessel patency in the presumed setting of chronic embolization. Marty 23 found that lysis was unsuccessful in 23% of the patients they treated with thrombosed aneurysms. In light of the dismal bypass results in these patients after unsuccessful lysis, primary amputation rather than revascularization was suggested.…”
Section: The Acutely Thrombosed Aneurysmmentioning
confidence: 97%